The Intergenerational Transmission of Health in Early Childhood - Katja Coneus; C. Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The prevalence and importance of children's physical health problems have been increasingly recognized in recent years. Physical health problems of children such as obesity, motor impairment and chronic diseases cause social costs. Further, they can lead directly to adult physical health problems, which cause additional social costs. This paper examines the intergenerational link and transmission of both maternal and paternal health on children's health in Germany. We investigate this issue using data from the German Socio-Economic Panel (SOEP), making particular use of the mother and child questionnaires. These data allow us to capture a broad set ofhealth measures: anthropometric, self-rated health and "more objective" health measures. The results indicate significant relationships between parental and child health in the first and third year of life. In order to take into account the endogeneity of parental health, we estimate fixed effect models. Overall, we find, controlling for parental income, education and family composition, that parents who experience poor health have children with significantly poorer health. For example, the father's bodymass index (BMI) is a predictor for their children's BMI. Mothers who consider their health as good, have also healthier children.
Keywords: I1; I12; J13; 330; Intergenerational transmission; child health; parental health; early childhood